2017
DOI: 10.1017/hpl.2016.46
|View full text |Cite
|
Sign up to set email alerts
|

Research and development of new neodymium laser glasses

Abstract: This work presents a brief introduction on three kinds of newly developed $\text{Nd}^{3+}$ -doped laser glasses in Shanghai Institute of Optics and Fine Mechanics (SIOM), China. Two $\text{Nd}^{3+}$ -doped phosphate glasses with lower thermal expansion coefficient and thermal shock resistance 4 times higher than that of N31 glass are developed for laser processing. Nd:Silicate and Nd:Aluminate glasses with peak emission wavelength at 1061 and 1065 nm, effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 24 publications
1
21
0
2
Order By: Relevance
“…Since the first laser demonstration of Nd 3+ ‐doped barium crown glass by the Snitzer in 1960s, Nd 3+ ‐doped laser glasses have been a hot topic and present a great significance in different fields, such as solid‐state laser, atmosphere monitoring, and optical sensing . Especially, Nd 3+ ‐doped phosphate laser glasses have been attracting much research interest and widely investigated owing to the advantages of high solubility of rare earth (RE) ions, excellent spectroscopic properties, and large damage threshold . The commercial Nd 3+ ‐doped phosphate laser glasses such as N31 (SIOM China), LGH‐8 (Hoya Japan) and LG‐770 (Schott America) have been successfully applied in high peak power laser system .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first laser demonstration of Nd 3+ ‐doped barium crown glass by the Snitzer in 1960s, Nd 3+ ‐doped laser glasses have been a hot topic and present a great significance in different fields, such as solid‐state laser, atmosphere monitoring, and optical sensing . Especially, Nd 3+ ‐doped phosphate laser glasses have been attracting much research interest and widely investigated owing to the advantages of high solubility of rare earth (RE) ions, excellent spectroscopic properties, and large damage threshold . The commercial Nd 3+ ‐doped phosphate laser glasses such as N31 (SIOM China), LGH‐8 (Hoya Japan) and LG‐770 (Schott America) have been successfully applied in high peak power laser system .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, Nd 3+ ‐doped phosphate laser glasses have been attracting much research interest and widely investigated owing to the advantages of high solubility of rare earth (RE) ions, excellent spectroscopic properties, and large damage threshold . The commercial Nd 3+ ‐doped phosphate laser glasses such as N31 (SIOM China), LGH‐8 (Hoya Japan) and LG‐770 (Schott America) have been successfully applied in high peak power laser system . Yet, different from the d‐d and p‐p transition of transition and main group metal ions with tunable emission, the luminescence of RE ions originated from f ‐ f transition is relatively insensitive to the surrounding environment .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increase in laser energy and the expansions of the laser driver's scale, the cleanliness of the working environment with numerous optical elements has greatly affected the construction cycle and operating life of the high power solid-state laser driver [1][2][3][4] . Recent studies have shown that flashlamp illumination is a major factor causing damage to the lasing media (slab or disk) when the contaminant particles deposit onto the surface of the optical element in a multi-segment Nd:glass disk laser amplifier [5][6][7][8] . Because the full fluence of the flashlamp illumination in SG-II can reach 10 J/cm 2 , most contaminant particles on the surface of the lasing media will be melted or decomposed.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] These optics not only require a surface figure with high precision but also need specific requirements for the wavefront distortion in the medium and high spatial frequencies. The conventional continuous polishing utilizes a large pitch lap, which usually covers the entire optic surface during the polishing process.…”
mentioning
confidence: 99%
“…The amount of the material removed in each cycle is calculated by repeating the Eqs. (3) and (4). Figure 6 shows the simulation results (using computer) based on the above model.…”
mentioning
confidence: 99%